PENERAPAN MODEL PEMBELAJARAN INKUIRI SOSIAL UNTUK MENINGKATKAN KETERAMPILAN SOSIAL SISWA SEKOLAH DASAR - Silvia Ediora; M. Syahrul Rizal; Rizki Ananda; Iis Aprinawati; Yenni Fitra Surya (Center for Research and Community Service (LPPM) University of Abulyatama, 2024)
This research was motivated by the low social skills of fifth grade students at SD Negeri 017 Ranah Singkuang. This study aims to improve the social skills of fifth grade students at SD Negeri 017 Ranah Singkuang, with a total of 25 students. The research used was Classroom Action Research (PTK) which was carried out in two learning cycles. Each cycle consists of two meetings and four learning stages, namely: planning, implementing, observing, and reflecting. Data collection techniques in the form of documentation, observation and tests. While the data analysis technique uses qualitative analysis and quantitative analysis. Based on the results of data analysis, the social skills of class V students at SD Negeri 017 Ranah Singkuang were obtained in the pre-action with a learning mastery percentage of 40%. In cycle 1 meeting I with a learning completeness percentage of 60% and in cycle 1 Meeting II there was an increase with a learning completeness percentage of 76%. In cycle 2 the first meeting also increased with a learning completeness percentage of 84%, and in cycle 2 the second meeting experienced another increase with a learning completeness percentage of 96%. Thus it can be concluded that by applying the social inquiry learning model it can improve the social skills of fifth grade students at SD Negeri 017 Ranah Singkuang.